Dual‐loop antennas with an expanded axial ratio bandwidth - Hirose, Kazuhide; Nishino, Koki; Nakano, Hisamatsu (Electronics letters, 2023)
The authors propose a novel dual‐wire antenna with a balanced feed to increase a 3‐dB axial ratio bandwidth. The antenna comprises loop elements with quasi two‐sources, and the effects of the element distance on the axial ratio bandwidth are revealed using the method of moments (MoM). It is found that the antenna has a maximum bandwidth of 41% at a distance of 0.15 wavelengths, three times as wide as that of an isolated loop element. Subsequently, the balanced feed is changed to a quasi‐balanced one using L‐figured parallel feedlines. It is found numerically and experimentally that the antenna shows an axial ratio bandwidth of 28%. We propose a novel dual‐wire antenna to increase a 3 dB axial ratio bandwidth. The antenna comprises loop elements with quasi two‐sources, and the effects of the element distance on the axial ratio bandwidth are revealed using the method of moments.